Modernizacja przestrzeni. Recepta na sukces = Modernizing Space: A Recipe For Success - Langner-Kosmaty, Agnieszka (Zielona Góra: "Pro Libris" Wydawnictwo Wojewódzkiej i Miejskiej Biblioteki Publicznej w Zielonej Górze)
A library can be a narrative told by a designer, a librarian, or sometimes even local government officials. Often, the greatest challenge is finding a common language. In Krosno Odrzańskie, a shared vision was realized that took into account the expectations of both older and younger users. On April 25, 2019, the new home of the Mediateka ? Public Library in Krosno Odrzańskie was officially opened. The library?s space is open but divided into zones dedicated to thematic activities and users of different age groups. The article describes the preparations for the project and presents its final results, highlighting both newly initiated and ongoing library initiatives.
Keywords: mediateka; biblioteka publiczna; Krosno Odrzańskie; strefy; przebudowa; media library; public library; zones; renovation